Preparation and thermophysical properties of graphite flake-carbon fiber coreinforced copper matrix composites. (31st December 2021) - Huang, Junchen; Miu, Guodong; Liu, Tongle; Huang, Chen; Guo, Shibo; Liu, Qian
Abstract: Graphite flake-carbon fiber coreinforced copper matrix composites were prepared by vacuum hot pressing technology. The carbon fibers were dispersed ultrasonic in alcohol and then mixed with graphite flake and alloys powder (Zr and Cu) for hot pressing sintering. The effects of the carbon fiber content on the microstructure, bending strength and thermal conductivity of the composites were investigated. The results show that the interface of the composites is well bonded. When the volume fraction of carbon fiber is 1%–3%, the carbon fiber can be uniformly dispersed in the matrix, and the bending strength of the composites can be improved effectively. When the volume fraction of carbon fiber is 2%, the bending strength reaches a maximum of 152 MPa, which is an increase of 60% compared with that of the composites without carbon fiber. However, an excessive addition of carbon fiber (4% or more) leads to an uneven distribution of carbon fiber, and the bending strength of the composites decreases. When the volume fraction of carbon fiber is 2%, the thermal conductivity of the composite is 597 W·m −1 ·K −1 . The acoustic mismatch model (AMM) associated with the Digimat MF module is able to predict the thermal conductivity of the anisotropic multiphase composites.